Effects of red clover (Trifolium pratense) isoflavones on the lipid profile of perimenopausal and postmenopausal women—A systematic review and meta-analysis. (February 2020) - Kanadys, Wieslaw; Baranska, Agnieszka; Jedrych, Marian; Religioni, Urszula; Janiszewska, Mariola
Highlights: Red clover has gained popularity as a treatment for menopausal symptoms because it is structurally and functionally similar to 17-estradiol. The results of this systematic review and meta-analysis suggest a favourable effect of red clover on lipid metabolism. Taking Trifolium pratense during menopause can modify abnormal cholesterol levels. Abstract: Aim: The aim of this systematic review and meta-analysis was to clarify the effect of a specific standardised extract of red clover ( Trifolium pratense ) on the lipid profile of perimenopausal and postmenopausal women. Methods: Medline (PubMed), EMBASE, and Cochrane Library electronic databases were searched for papers in English reporting randomized controlled trials published up to 2017. Reference lists from those papers were checked for further relevant publications. Studies were identified and reviewed for their eligibility for inclusion in this review. The changes from baseline in the levels of individual components of the lipid profiles were used to assess differences between the active treatment and placebo groups. Weighted mean differences and 95 % confidence intervals were calculated for continuous data using a random-effects model. Results: Ten eligible studies (twelve comparisons) with 910 peri- and postmenopausal women were selected for systematic review. The meta-analysis showed changes in serum levels: total cholesterol, −0.29 (95 % CI: −0.53 to −0.06) mmol/L [–11.21 (95 % CI: –20.49 to –13.92) mg/dL], p = 0.0136; LDL-cholesterol, −0.13 (95 % CI: −0.35 to 0.09) mmol/L [–5.02 (95 % CI: –13.53 to 3.48) mg/dL], p = 0.2418; triglycerides, −0.15 (95 % CI: −0.32 to 0.01) mmol/L [–13.28 (95 % CI: –28.34 to 0.88) mg/dL], p = 0.0592; and HDL-cholesterol, 0.14 (95 % CI: −0.08 to 0.36) mmol/L [5.41 (95 % CI: –3.09–13.92) mg/dL], p = 0.2103. The I 2 statistic ranged from 87.95%–98.30 %, indicating significant heterogeneity. Conclusions: The results suggest that a red clover extract is efficacious in reducing the concentrations of total cholesterol; however, changes in HDL-C, LDL-C and triglycerides are not as pronounced. Potentially, this means that women taking Trifolium pratense for menopausal symptoms can derive additional benefits from the plant's specific effect that corrects abnormal cholesterol levels. Additional studies are needed to assess its effects on post-menopausal women.